2015
DOI: 10.1016/j.sbspro.2015.04.100
|View full text |Cite
|
Sign up to set email alerts
|

Changing Pre-service Primary-school Teachers’ Attitude Towards Mathematics by Collaborative Problem Solving

Abstract: Primary school teachers' attitude towards Mathematics influences their pupils' attitude. A pupil with a positive attitude is more likely to develop his/her mathematical problem solving skills, thus developing a positive attitude towards Mathematics in case of pre-service primary school teachers is very important. This paper presents the results of a research on de efficiency of collaborative problem solving in changing pre-service primary school teachers attitude towards Mathematics. During the intervention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Adediwura [ 23 ] describes attitude as a persons’ positive, neutral or negative thinking about mathematics. A positive attitude is very instructive because research shows that there is a link between student performance and their attitude toward mathematics [ 24 ]. Students who have a positive attitude toward mathematics have better problem-solving abilities and are better able to resolve unusual difficulties [ 25 ].…”
Section: Theoretical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adediwura [ 23 ] describes attitude as a persons’ positive, neutral or negative thinking about mathematics. A positive attitude is very instructive because research shows that there is a link between student performance and their attitude toward mathematics [ 24 ]. Students who have a positive attitude toward mathematics have better problem-solving abilities and are better able to resolve unusual difficulties [ 25 ].…”
Section: Theoretical Reviewsmentioning
confidence: 99%
“…According to some of the findings, having a negative attitude toward mathematics is associated with minor academic consequences in college students [ 39 , 40 ] and children [ 7 ]. However, in addition to doing so, Zsoldos-Marchis [ 24 ] investigated the problem-solving potential of various primary preschool teachers’ attitudes toward mathematics.…”
Section: Theoretical Reviewsmentioning
confidence: 99%
“…Therefore, many problems in problem solving teaching for preservice mathematics teachers need to be discussed in depth. Zsoldos-Marchis (2015) studied the effectiveness of collaborative problem solving in changing the attitudes of preservice elementary teachers toward mathematics. They found that students who used cooperative learning methods had statistically significant positive changes in their enjoyment of mathematics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Handful studies have been made to find out the factors affecting students' performance in the subject in both basic and tertiary educations (Peteros et al, 2019). Most of the studies found that students' performance in mathematics is influenced by students' attitude towards the subject, knowledge, teaching strategies, classroom environment, gender stereotypes (Mohamed et al, 2011;Zsoldos-Marchis, 2015;Acharya, 2017). Accordingly, there is limited interest that is focused on how the at-risk students in mathematics are coping and learning in a printed modular approach (Fong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%